Security vulnerabilities on implantable medical devices - Longras, Ana (2022)
Implantable medical devices are used for critical functions like diagnosis, prevention, control, treatment or lifeenhancing patients with chronic diseases, through diagnosing and/or monitoring for better care and quality of patients' lives. Communication between medical devices and healthcare professionals is of utmost importance to treat health data and critical functions without the need for patient surgery. Increasingly, the development, implementation and use of security mechanisms that can provide the availability of information, the integrity of medical devices and the confidentiality of data are needed. Alteration of data, theft, improper access to this information, or even denial of service in a healthcare system can lead to the death of patients on devices such as these essential to life. This paper mainly contribution is a research on implantable medical device vulnerabilities and attack mitigation strategies.